Settlement Of Divorce Dispute Through The Forum Of Mediation In Judicial Institutions As An Effort Of Legal Protection For The Rights And Interests Of The Child Of Post-Divorce - Ismail Rumadan; Ummu Salamah (Universitas Islam Negeri Antasari Banjarmasin, 2021)
Abstrak: Secara yuridis sudah ada pengaturan dalam Undang-undang Perkawianan Nomor. 1 tahun 1974 Pasal 41 tentang pemeliharaan hak anak akibat perceraian. Namun dalam prakteknya sering terjadi perebutan atas hak pemeliharaan anak. Perebutan atas hak pemeliharaan anak ini kerap terjadi dikarenakan masing-masing pihak (orang tua) merasa memiliki hak untuk dapat merawat anak-anaknya. Dengan adanya PERMA Nomor 1 tahun 2016 tentang Presedur Mediasi di Pengadilan maka diharapkan penyelesaian sengketa perkawinan melalui forum mediasi dapat memberikan perlindungan hukum terhadap hak dan kepentingan anak. Tujuan penelitian ini untuk dapat mengkaji upaya dalam dalam mewujudkkan perlindungan hukum terhadap hak dan kepentingan anak pascapercaian melalui forum mediasi. Hasil kajian menunjukkan bahwa pola penyelesaian sengeketa perceraian melalui forum mediasi dapat memberikan perlindungan terhadap hak dan kepentingan anak dengan kesepakatan yang dibuat oleh para pihak (orang tuanya) yang tertulis dalam akta perdamaian. Metode dalam penelitian ini adalah penelitian hukum normative, setelah mengkaji sumber data yang didapatkan melalui kepustakaan juga menelaah hasil mediasi di Pengadilan Agama yang terdapat dalam Akta Perdamaian.Kata Kunci: mediasi, peradilan, Akta Perdamaian Abstract: Legally, there is already a regulation focusing on Marriage Law, namely Law 1 of 1974 article 41concerning child care due to divorce. However, in practice there are struggles to take care of children’s right. This struggle over the children right occurs because each parents feels that they have the right to be able to take care of their children. With the PERMA Number 1 of 2016 concerning court mediation procedures, it is hoped that resolving marital disputes through mediation forums can provide legal protection for children's rights. The purpose of this study is to examine efforts in realizing legal protection for the rights and interests of post-divorce children through mediation forums. The results of the study show that the pattern of resolving divorce disputes through mediation forums can provide protection for the rights and interests of children with an agreement made by the parents written in the peace deed. The method in this research is normative legal research after reviewing the sources of data obtained through the literature, it also examines the results of mediation in the Religious Courts contained in the Peace Deed.Keywords: Mediation, Judicial, Settlement Agreement